2016
DOI: 10.6061/clinics/2016(08)07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors of post-chemoradiotherapy as valuable indicators for pathological complete response in locally advanced rectal cancer

Abstract: OBJECTIVES:Pathological complete response has shown a better prognosis for patients with locally advanced rectal cancer after preoperative chemoradiotherapy. However, correlations between post-chemoradiotherapy clinical factors and pathologic complete response are not well confirmed. The aim of the current study was to identify post-chemoradiotherapy clinical factors that could serve as indicators of pathologic complete response in locally advanced rectal cancer.METHODS:This study retrospectively analyzed 544 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
2
19
0
5
Order By: Relevance
“…Rombouts et al studied 1073 patients with LARC and revealed that radiotherapy-surgery intervals of 9 to 12 weeks resulted in a high pCR rate [37]. Some studies have reported that post-CRT clinical factors were associated with pCR [23,38]. In the current study, several post-CRT variables were analyzed and post-CRT CEA ≤2 ng/mL was an independent predictor of increased pCR rates.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Rombouts et al studied 1073 patients with LARC and revealed that radiotherapy-surgery intervals of 9 to 12 weeks resulted in a high pCR rate [37]. Some studies have reported that post-CRT clinical factors were associated with pCR [23,38]. In the current study, several post-CRT variables were analyzed and post-CRT CEA ≤2 ng/mL was an independent predictor of increased pCR rates.…”
Section: Discussionmentioning
confidence: 55%
“…CEA is associated with prognosis and treatment response in patients with LARC treated with neoadjuvant CRT [39]. Deceased post-CRT CEA levels have been reported to be associated with increased pCR rates in LARC patients following neoadjuvant CRT [38,40]. Lowering post-CRT CEA levels might imply decreased tumor burdens and therefore, a favorable response to CRT was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown predictive value of post-CRT CEA levels in patients with LARC treated with neoadjuvant CRT. Peng et al [25] revealed that a post-CRT CEA levels ≤ 2 ng/ml was an independent predictors for pCR (OR = 1.57, 95% confidence interval [CI],…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In addition, 20-30% of patients successfully achieve pathological complete response (pCR) after preoperative CRT, which indicates a favorable prognosis. [5][6][7] Nevertheless, pCR does not absolutely represent disease-free survival (DFS) after radical treatment, in that 7.7-11% of patients ultimately develop distant metastasis postoperatively. 8,9 Accurate pathological staging is important to determine the recurrence risk and thus provide guidance for postoperative treatment decisions.…”
Section: Introductionmentioning
confidence: 99%